PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VII SMP NEGERI 7 PADANG - Sari, Meilia (Jurnal Edukasi dan Penelitian Matematika, 2023)
Research on the effects of the Problem Based Learning (PBL) model on the mathematical problem solving skills of grade VII SMPN 7 Padang. This skill is crucial. Observations at this school showed that this skill is still low. Therefore, PBL-based research was conducted to improve this skill. A posttest-only non-equivalent control group design was used in this pseudo-experiment. This study involved the seventh grade of SMPN 7 Padang TP 2022/2023. Data analysis rejected H0 because the P-value was 0.017. Thus, PBL had an effect on math problem-solving skills compared to direct learning.Keywords– Mathematical Problem Solving, Hands-On Learning, PBL